Representasi Maskulinitas Perempuan Moonbyul melalui Gaya Berpakaian pada Vidio Klip’eclipse’ dalam Perspektif Semiotika Saussure - Maila Putri Kirana; Ni Putu Intan Permatasari (Yayasan Literasi Sains Indonesia, 2025)
The globalization of K-Pop, or what is referred to as the hallyu wave, has become a forum to raise social issues, one of which is gender equality. South Korea is still experiencing gender equality issues, but artists in the music industry are actively opposing traditional gender norms. This research aims to elaborate the representation of masculinity shown by K-Pop artist Moonbyul through his style of clothing in the Music Video 'Eclipse' from the perspective of Ferdinand de Saussure's semiotics. With a qualitative descriptive approach, primary data in the form of visual and symbolic observations on the masculine style of dress depicted by Moonbyul in the Music Video 'Eclipse', supported by secondary data through interviews by informants with criteria that have been selected through purposive sampling techniques and also literature data. The results of the study show that Moonbyul uses traditional masculine clothing such as suits, boots, and camouflage equipment, which is contrary to the stigma of female idol dressing style in general which is light-colored and tight. Moonbyul fashion is seen as a sign that conveys a meaning of masculinity to women, which is analyzed through Ferdinand de Saussure's concept of semiotics that is signifier and signified. This indicates a shift in meaning regarding traditional gender stigma. This deconstruction is in line with the Sustainable Development goals by the United Nations, namely SDGs point 5 regarding gender equality.